British foreign policy and the Anglican Church Christian engagement with the contemporary world - Blewett, Timothy; Hyde-Price, Adrian G. V.; Rees, G. Wyn 1963- (Aldershot [u.a.] Ashgate, 2008)
The ethical context -- Introduction / Tim Blewett -- Christian ethics and the dilemmas of foreign policy / Adrian Hyde-Price -- The military instrument -- The continuing, crucial relevance of just war criteria / Richard Harries -- Balance of consequences : towards an ethical standpoint on the Iraq intervention of 2003 / Richard Bonney -- Three parables about war / Charles Jones -- British military intervention since 1990 / Tim Cross -- The church and the war on terror / Richard Lock-Pullan -- UK arms sales and the Church of England / Wyn Rees -- Britain and the less developed world -- Waiting for jubilee : the campaign for debt cancellation / Timothy Jones -- The challenge of aid / Fletcher Tembo
Includes bibliographical references
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: Church of England -- Doctrines; Christianity and politics -- Church of England -- History -- 20th century; Church and state -- Church of England -- History -- 20th century; Christianity and international relations; Great Britain -- Foreign relations; Aufsatzsammlung